IMPLEMENTASI MDLC (MULTIMEDIA DEVELOPMENT LIFE CYCLE) DALAM PEMBUATAN MULTIMEDIA PEMBELAJARAN KITAB SAFINAH SUNDA - Deris Septian; Yenni Fatman; Siti Nur (Jurnal Computech & Bisnis (e-Journal), 2021)
Safinah Book is a book that contains material jurisprudence, the work of Sheikh Salim Bin Sumair Al-Hadhromiy, until now it is still frequently studied by Muslims both in villages and in cities. Learning the Safinah Book is an important thing for Muslims.This book consists of 6 chapters, namely: chapter of monotheism, chapter of thaharoh, chapter of prayer, chapter of janazah, chapter of zakat and chapter of fasting. Because it is supported by rapidly increasing technological developments, finally all human activities can be assisted by digital media, this is certainly true in the field of Islamic religion. Therefore, researchers realized the importance of this occasion, to create an application that can be used anywhere and anytime as a learning tool for the Safinah book independently. This application development using methods developed MDLC (Multimedia Development Life Cycle) version of the Luther-Sutopo. This research produces a product multimedia learning of the Safinah Sunda book based on Android designed using Adobe Animate software. Keywords : Book of Safinah, Multimedia Learning, MDLC, Android, Adobe Animate.DOI : http://doi.org/10.5281/zenodo.4958220